Do you teach the way you were taught? Graduate teachers perception of their undergraduate teacher preparation at the university - Umar, Mwembesa; Syed Hassan, Sharifah Sariah; Hashim, Che Noraini; Preece, Abdul Shakour Duncan (2014)
This research study eva luated the effectiveness of the Bachelor of Arts Education (BA.Ed.) in preparing secondary school teachers. Using the views of the Graduate teachers the study focused on two issues; Firstly, the theoretical coverage of four selected aspects of the pedagogi cal curriculum namely; classroom organization and management, lesson structure, skills and techniques of teaching and teaching methods. Secondly, the perceived teaching practices of graduate teachers in their secondary school classrooms. Two hundred and se venteen graduate teachers who completed the programme in 2007, 2008 and 2009 from the Islamic university in Uganda participated in this study. The study used Process and Product of the Stufflebeam‘s CIPP evaluation model through a mixed method research des ign of quantitative and qualitative approaches. The data was analysed using Pearson - Product moment correlation, MANOVA tests, descriptive statistics and coding of themes. The results show that most areas of classooroom organization and management received more than adequate coverage including; ability to address students‘ differences in the classroom, ability to handle studnts‘ discipline and ability to engage students. However, results show that the following areas reeived less than adequate coverage; desi gning computer - based learning materials in a lesson, Ability to use computer - based teaching skills and Projet method. The study discovered that there is a strong relationship between theory of coverage and graduate teachers‘ practices in all the selected a spects of the pedagogical curriculum. The qualitative research findings show that 56% of graduate teachers do not use lesson planning in their classrooms because they regard it is time wasting . It was discovered that gender does not have statistically sign ificant effect on practicing aspects of the pedagogical curriculum. The descriptive statistics show that; History teachers conduct their classes in a better organized and managed classroom than IRE teachers. The graduate teachers of 2008 practice these asp ects more than graduate teachers of 2007 and 2009. The level of practice of graduate teachers of 2007 in all aspects is less than those who graduated in 2008 and 2009. The study recommends among others; regular programme evaluation, organizing regular refr esher programmes for BA.Ed graduate teachers and evaluation of teacher candidates‘ teaching knowledge and skills before graduation.